Inovasi Pembelajaran Penulisan Naskah Drama Anak dengan Menggunakan Strategi IDCD dan Implementasinya dalam Merdeka Belajar - Veronika Unun Pratiwi; Muhammad Rohmadi (UIR Press, 2022)
Writing is one of the four aspects of language skills. Writing is a form of indirect communication that expresses the author's intentions. In writing a drama script, there are 3 essential things that must be mastered. The advantages of writing scripts for children are not as real as the real conditions in the field. At least students write children's scripts, and it's not because they don't like children's scripts. But because they do not understand who the child is and how. To overcome this, the authors apply the IDCD strategy (Identification, Design, Change, and Development) and its implementation in Merdeka Learning. The method used is a qualitative descriptive method, based on a literature review. The results achieved by using this IDCD strategy are. This strategy has four main stages: defining, designing, modifying, and developing. This strategy creates a good storyline and is in accordance with the developmental level of the child, but for good results the time needed is relatively long term.